2016
DOI: 10.3892/ijmm.2016.2819
|View full text |Cite
|
Sign up to set email alerts
|

Microarray expression profiles of genes in lung tissues of rats subjected to focal cerebral ischemia-induced lung injury following bone marrow-derived mesenchymal stem cell transplantation

Abstract: Ischemia-induced stroke is the most common disease of the nervous system and is associated with a high mortality rate worldwide. Cerebral ischemia may lead to remote organ dysfunction, particular in the lungs, resulting in lung injury. Nowadays, bone marrow-derived mesenchymal stem cells (BMSCs) are widely studied in clinical trials as they may provide an effective solution to the treatment of neurological and cardiac diseases; however, the underlying molecular mechanisms remain unknown. In this study, a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…As previously reported, stroke could lead to neurological dysfunction (Sun et al, 2010;Hu et al, 2017;Jain et al, 2017), and the process of stroke had the participation of neuronal apoptosis (Li et al, 1999). In this study, we found that brain infarction was obvious with TTC staining and Longa score confirmed the neurological deficit in MCAO rats.…”
Section: Discussionsupporting
confidence: 75%
“…As previously reported, stroke could lead to neurological dysfunction (Sun et al, 2010;Hu et al, 2017;Jain et al, 2017), and the process of stroke had the participation of neuronal apoptosis (Li et al, 1999). In this study, we found that brain infarction was obvious with TTC staining and Longa score confirmed the neurological deficit in MCAO rats.…”
Section: Discussionsupporting
confidence: 75%
“…Microarray was used to investigate differentially expressed lncRNAs and mRNAs which then become the main data for the subsequent bioinformatics analyses of the study. This working strategy has been applied and validate in studying many diseases including cancer ( Han et al, 2018 ; Liang et al, 2018 ; Lou et al, 2018 ), cerebral ischemia-induced lung injury ( Hu et al, 2017 ), and traumatic brain injury ( Lyu et al, 2017 ). In our study, microarray was used to study the changes in expression of lncRNAs and mRNAs in POCD group.…”
Section: Discussionmentioning
confidence: 99%
“…GO analysis has illuminated the functions of genes through biological process, cellular component, and molecular function. While KEGG is normally used to study the possible roles of expressed RNA with correlation to cell signaling pathways ( Hu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This technology can quickly and accurately analyze high-level information, and it provides the important theoretical basis for sequence analysis, gene expression, and genome research. 7 In recent years, various public free chip databases can be used by researchers on the Internet for in-depth research. However, single PNET chip analysis may result in statistical deviation, and then lead to results that are not accurate enough.…”
mentioning
confidence: 99%
“…At present, gene chip technology has been widely used in the diagnosis and treatment of diseases. This technology can quickly and accurately analyze high-level information, and it provides the important theoretical basis for sequence analysis, gene expression, and genome research 7. In recent years, various public free chip databases can be used by researchers on the Internet for in-depth research.…”
mentioning
confidence: 99%